Discrete squeezed states for finite-dimensional spaces - Marchiolli, Marcelo A. [UNESP]; Ruzzi, Maurizio [UNESP]; Galetti, Diógenes [UNESP] (American Physical Society (APS), 2007)
We show how discrete squeezed states in an N2 -dimensional phase space can be properly constructed out of the finite-dimensional context. Such discrete extensions are then applied to the framework of quantum tomography and quantum information theory with the aim of establishing an initial study on the interference effects between discrete variables in a finite phase space. Moreover, the interpretation of the squeezing effects is seen to be direct in the present approach, and has some potential applications in different branches of physics. © 2007 The American Physical Society.